A revisit of pecking order theory versus trade-off theory: Evidence from Pakistan - Muhammad Azeem Qureshi; Nadeem Ahmed Sheikh; Aftab Ahmad Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The objective of this study is to investigate which of the two competing theoretic frameworks; pecking order theory (POT) or trade-off theory (TOT); better explains the corporate leverage behaviour in Pakistan. For this purpose, we use fixed effects model on a large unbalanced panel data comprising of 13,026 firm-year observations of non-financial firms listed on Karachi Stock Exchange Pakistan during 1972-2010 Our results indicate that leverage has two pervasive and significant relationships. First, leverage is negatively related to current and past profitability. Second, leverage is positively related to past dividends. In addition, empirical results present a reasonable support to POT regarding growth. However, POT gets nominal empirical support in Pakistan regarding firm size. The results of this study will help the corporate managers to better formulate the leverage policy.
Keywords: 330; leverage; pecking order theory; trade-off theory; Pakistan